Pelayanan Cepat Tanggap Administrasi Kependudukan Berbasis Masyarakat Di Desa Keroya - Fahruddin Fahruddin; Roza Wildani; Winda Kartika Sari (Unram Journal of Community Service, 2021)
Keroya Village is one of the villages of Aikmel District, which is included in the area of East Lombok Regency. The population of Keroya Village in 2019 was 3,916 people, with 1,381 families. Keroya Village is a village created by the division of Desa Kembang Kerang. The Keroya village was split in 2011 and was officially recognized in 2012. With the division, it can trigger problems in the population administration section. Such as making KTP services, birth certificates, death certificates, and family cards. The implementation of the Thematic KKN, which was carried out for 45 days, aims to increase public awareness of the importance of the Population Administration document. This is done by carrying out the main program of Community Based Population Administration Rapid Response Services in the Village of Keroya. The program begins with socialization, data collection, file collection, services, and finally, distribution. It is hoped that from this activity, the community will start to pay attention to the importance of the Adminduk document and the impact of not having Adminduk